Studenti sobě - Studentské centrum Poříčí - Mareš, Martin (Vysoké učení technické v Brně. Fakulta architektury)
Uzavření bloku zástavbou inspirující se historickou strukturou staveb a jejich zásadami. Příjemné prostředí pro studentské bydlení ve styku s přírodou téměř v centru města. Sklonité střechy prostříhnuté ŽB boxy tvořící rytmus na fasádě.

Block closure by the building inspirated by historical town system. Nice location fo student housing in touch with nature near to center of town. Historical styled building penetrated by the new aged concrete boxes.
The Students themselves - Student Center Poříčí
Keywords: tradiční zástavba; historický kontext; lepší fungování městské lokality; příjemný studentský život; různé možnosti a členění ubytovacích jednotek; menza; historic context; better feeling in this part of town; pleasant student living; several variation of living; student canteen; nice look-out to townscape